Geneza herezji wczesnochrześcijańskich w ujęciu Filastriusza z Brescii - Szram, Mariusz (Vox Patrum, 2016)
The original Latin catalogue of heresies, produced by Saint Philastrius of Brescia in the second half of IVth century, encompasses several observations regarding the source of early Christian heterodox movements. These views are dispersed and interwoven into the analysis of particular heresies, and as such do not constitute an integral and standalone teaching on the nature of unorthodoxy and its genesis. The present work attempts at enucleating this standpoint and summarising it in a comprehensive and complementary manner. Regarding the issue of the foundation of heresy, Philastrius proposed his own point of view based on the following threefold argumentation: the theological (Satan is the father of all the world’s heterodoxy – comprehended as a lapse form God’s truth), the moral (heresies rise due to one’s pride), and historical and cultural (errors in early Christian doctrine derive from the Judaic sects or else from the counterfactual views of the ancient Greek philosophers). Philastrius’ perspective refers back to an extensive and modestly younger work Panarion by Epiphanius of Salamis, in which the topic of Jewish-deriving deviations from the doctrine was treated even more at length. The Bishop of Brescia’s index has been the inspiration for the later catalogues of unorthodoxy by St. Augustine (narrow in the topic of Judaic origins of heretical movements and rather focused on influences from the ancient philosophical schools) and Isidore of Seville (intermingling both sources of early heretical movements – i.e. Judaic and Greek – withholding the determination which of them has in fact more influenced the uprising of heterodoxy and the doctrine itself).